2020
DOI: 10.1007/s10096-020-03944-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Porphyromonas gingivalis involved in Parkinson’s disease?

Abstract: Porphyromonas gingivalis, a major subgingival plaque bacterium in periodontitis, has recently attracted much attention as a possible microbial driver in Alzheimer’s disease. In the present paper, another common neuroinflammatory disease, Parkinson’s disease (PD), is discussed. A recent study found major virulence factors of P. gingivalis such as gingipain R1 (RgpA) and lipopolysaccharide in the blood circulation of a PD population. The current review reveals how features such as systemic inflammation, hypercoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 61 publications
0
24
0
8
Order By: Relevance
“…377 A recent hypothesis is that besides causing oxidative stress, iron dyshomeostasis reactivates dormant microbes in the gut and other tissues, which results in systemic inflammation as well as shedding of potent inflammagens, such as lipopolysaccharides, which along with genetic susceptibilities play a key role in the pathogenesis of AD (as well as other neurodegenerative diseases, such as PD). [378][379][380][381][382] Inflammation resulting from microbial products causes cell damage releasing ferritin, which may provide an explanation for elevated serum ferritin in AD. Therefore, while serum ferritin can represent a measure of liver iron and intracellular iron content, it may also a be a marker of inflammation.…”
Section: Age-associated Neurodegenerative Diseasesmentioning
confidence: 99%
“…377 A recent hypothesis is that besides causing oxidative stress, iron dyshomeostasis reactivates dormant microbes in the gut and other tissues, which results in systemic inflammation as well as shedding of potent inflammagens, such as lipopolysaccharides, which along with genetic susceptibilities play a key role in the pathogenesis of AD (as well as other neurodegenerative diseases, such as PD). [378][379][380][381][382] Inflammation resulting from microbial products causes cell damage releasing ferritin, which may provide an explanation for elevated serum ferritin in AD. Therefore, while serum ferritin can represent a measure of liver iron and intracellular iron content, it may also a be a marker of inflammation.…”
Section: Age-associated Neurodegenerative Diseasesmentioning
confidence: 99%
“…In order to induce accumulation of Aβ, NF-κB-dependent cathepsin (Cat) B was needed for cleaving pro-IL-1 β and processing AβPP [35]. This probably caused presence of amyloid (fibrin (ogen) in the blood plasma of these patients, which may have affected the development of PD [11,43].…”
Section: Relationship Between Porphyromonas Gingivalis and Amyloidosismentioning
confidence: 99%
“…recent study reported major virulence factors of P. gingivalis such as gingipain R1 (RgpA) and LPS in the circulation of PD patients[11]. This may have induced systemic inflammation, hyper coagulation, presence of amyloid (fibrin (ogen) in plasma and ultrastructural changes in the blood platelets of these patients[11,43].Possible role of amyloidosis in Alzheimer's diseaseIn AD, accumulation of amyloid beta (Aβ) and neurofibrillary tangles are major characteristics in the brain. Aβ is considered as a neurotoxic peptide[50].…”
mentioning
confidence: 99%
“…It is universally expressed in our cells and it is involved in a variety of physiological processes, including the innate immune response [41][42], and the chemical metabolism of xenobiotics [43]. Relevant scientific proves [44][45][46][47][48][49][50] have been brought in the latest years for the link between exposure to the pollution with those respirable particles containing those groups of substances and a plethora of diseases due to the dysregulation of defense mechanisms. The common sense rule points towards the fact that the more a pollutant processing biological entity is expressed in more different body cells the greater are chances that the homeostatic equilibrium to be disturbed somewhere down the road, when body clearance of the processed pollutant or its metabolites cannot be done properly.…”
Section: Pollution Landfill Effectsmentioning
confidence: 99%
“…This is a bacterium present almost always in subgingival plaque in periodontitis. Recent studies reported that it can be linked to the clinical pathological conditions like systemic inflammation, hypercoagulation, presence of amyloid fibrin (ogen) in plasma as well as structural changes in platelets, manifest in Parkinson disease patients [48,49]. Metal biochemistry in living organisms is governed especially by coordinative chemistry that allows the flexibility to realise local bonds depending on the cell necessities, assuring the extraordinary dynamics required by the energetic biochemical reactions.…”
Section: Pollutantsmentioning
confidence: 99%